The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1098/rstb.2012.0066
|View full text |Cite
|
Sign up to set email alerts
|

Subunit composition of CP43-less photosystem II complexes ofSynechocystissp. PCC 6803: implications for the assembly and repair of photosystem II

Abstract: Photosystem II (PSII) mutants are useful experimental tools to trap potential intermediates involved in the assembly of the oxygen-evolving PSII complex. Here, we focus on the subunit composition of the RC47 assembly complex that accumulates in a psbC null mutant of the cyanobacterium Synechocystis sp. PCC 6803 unable to make the CP43 apopolypeptide. By using native gel electrophoresis, we showed that RC47 is heterogeneous and mainly found as a monomer of 220 kDa. RC47 complexes co-purify with small Cab-like p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 56 publications
4
68
2
Order By: Relevance
“…After association of Ycf39, Hlips, and chlorophyll synthase, the D1 protein emerging from membrane-bound ribosomes will be loaded with the reused chlorophylls and finally bound to the D2 protein to form RCII* (Figure 7). After attachment of the CP47 module , the Ycf39-Hlip complex is detached from the resulting RC47 complex (Boehm et al, 2012a) and used for biosynthesis and assembly of other D1 modules. The sensitivity of PSII activity in the ycf39 null mutant to high light ( Figure 5A) suggests that the use of recycled chlorophyll for D1 biosynthesis might be especially important at the initial stages of high light stress when de novo biosynthesis of chlorophyll is not yet fully induced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After association of Ycf39, Hlips, and chlorophyll synthase, the D1 protein emerging from membrane-bound ribosomes will be loaded with the reused chlorophylls and finally bound to the D2 protein to form RCII* (Figure 7). After attachment of the CP47 module , the Ycf39-Hlip complex is detached from the resulting RC47 complex (Boehm et al, 2012a) and used for biosynthesis and assembly of other D1 modules. The sensitivity of PSII activity in the ycf39 null mutant to high light ( Figure 5A) suggests that the use of recycled chlorophyll for D1 biosynthesis might be especially important at the initial stages of high light stress when de novo biosynthesis of chlorophyll is not yet fully induced.…”
Section: Discussionmentioning
confidence: 99%
“…PSII assembly is initiated through interaction of the D1 and D2 modules to form a RC intermediate, termed the RCII complex. The CP47 module (Boehm et al, 2011) is then attached to RCII forming a CP43-less complex, called RC47 (Boehm et al, 2012a). Oxygen-evolving monomeric and dimeric PSII are formed after addition of the CP43 module (Boehm et al, 2011), attachment of the luminal extrinsic proteins, and light-driven assembly of the oxygen-evolving Mn 4 CaO 5 complex (Komenda et al, 2008;Nixon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Psb28 is found across a wide range of cyanobacteria and has homologs in higher plants, but relatively little is known about its binding site and function (18). Dobáková et al (19) found that Psb28 binds mainly to the monomeric CP43-less PSII assembly intermediate, referred to as "RC47," a finding confirmed subsequently (20)(21)(22). Although deletion of the psb28 gene had little physiological effect under typical growth conditions (19,20,22), its absence impaired PSII recovery after photodamage under high-light conditions, especially at high temperature (20), and under intermittent high-light/dark conditions (22), suggesting a critical role of this protein during increased PSII turnover.…”
mentioning
confidence: 93%
“…Binding of pre-CP47 to the RC forms the RC47 (CP43-less monomer). Concomitant attachment of pre-CP43 leads to the assembly of the PSII monomer and enables attachment of the oxygen-evolving complex (Rokka et al, 2005;Boehm et al, 2012;Komenda et al, 2012;Nickelsen and Rengstl, 2013). Following dimerization of the monomer, the outer chlorophyll a/b binding antenna proteins CP29, CP26, and CP24 and finally trimeric light-harvesting complex II (LHCII) proteins are attached to form the PSII supercomplexes (Kouril et al, 2012).…”
Section: Introductionmentioning
confidence: 99%